Peningkatan Pengelolaan Keuangan Melalui Pelatihan dan Pendampingan di Badan Usaha Milik Desa (BUMDes) Gampong Siem - Rizky, Fitrian; Agustina, Agustina; Azlina, Azlina; Lisnawati, Lisnawati; Azmy, Khairul; Sari, Dewi Maya; Martunis, Lukman (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
The financial management of Badan Usaha Milik Desa (BUMDes) is a vital aspect of local economic development in Indonesia. The implementation of Kepmendesa No. 136 of 2022 is an issue that must be considered by BUMDes Gampong Siem for the preparation and management of financial reports. This community service is carried out through activities related to the preparation and reporting of finances in accordance with Kepmendesa No. 136 of 2022. Based on the assistance and training provided, it was concluded that BUMDes Gampong Siem has not yet prepared and reported finances in accordance with Kepmendesa No. 136 of 2022. Currently, BUMDes Gampong Siem, whose main businesses focus on cattle breeding and a savings and loan cooperative, still uses a traditional financial recording system, which objectively does not allow for detailed access to business management and conditions. There is a need for trained human resources to regularly oversee and prepare financial reports for BUMDes in Gampong Siem.